Cognitive Representations of Future Self as Predictors of Motivational Impairment in Women with PTSD - Camilo Ríos, Juan; Abalorio, Bridget (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore how cognitive representations of the future self predict motivational impairment in women diagnosed with post-traumatic stress disorder (PTSD).Methods and Materials: Using a qualitative research design, the study employed a phenomenological approach to investigate the lived experiences of 25 women with clinically diagnosed PTSD residing in urban areas of Mexico. Participants were selected through purposive sampling from trauma recovery centers and interviewed using semi-structured formats. Interviews focused on perceptions of the future self, goal orientation, and motivational capacity. Thematic analysis was conducted following Braun and Clarke’s six-phase method, with data coding and organization supported by NVivo 14. Data collection continued until theoretical saturation was achieved.Findings: Three overarching themes emerged from the data: (1) Fragmented Future Self-Image, including subthemes such as fear-based future projections and absence of agency; (2) Trauma-Driven Motivational Impairment, characterized by emotional avoidance, loss of drive, and cognitive dissonance in goal setting; and (3) Reconstructive Possibilities Through Self-Insight, including the emergence of self-compassion, micro-motivation strategies, and support from interpersonal relationships. Participants reported a high degree of temporal disintegration, with future self-images often perceived as emotionally negative, unrealistic, or inaccessible. However, small-scale future planning and narrative reframing were identified as pathways for motivational recovery.Conclusion: The findings highlight that PTSD significantly alters cognitive representations of the future self, leading to motivational deficits rooted in fear, avoidance, and identity fragmentation. Nevertheless, therapeutic interventions that foster time perspective balance, future self-continuity, and compassionate self-narratives may restore agency and motivational engagement in trauma-affected women.